Pengaruh Celebrity Endorser JKT48 Terhadap Interaksi Hiperpersonal Pengikut Instagram Erigo - Viadi, Crista; Aji, Imanuel Deny Krisna (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2024)
Erigo is a fashion item brand that originates and is produced by local entrepreneurs. With advances in marketing communications in Indonesia, Erigo uses a marketing communications strategy by collaborating with JKT48 as a celebrity endorser. In this practice, business owners invite celebrities to use their products and publicize the experience on social media. This practice succeeded in attracting the attention of consumers so that it became a trend among society to use celebrity endorsers. This research aims to determine the influence of JKT48 celebrity endorsers on the hyperpersonal interactions of Erigo Instagram followers. This research was carried out using a descriptive quantitative method based on a causality hypothesis (cause and effect relationship). Overall 100 respondents participated as samples in this research. The results of this research show that JKT48 celebrity endorsers are able to influence the hyperpersonal interactions of followers of the @erigostore account